Judging French. Lay and expert language commentary in nineteenth- and twenty-first-century France - Humphries, Emma (2021)
This thesis presents a comparative study of French language commentary from two time periods, the late nineteenth and the early twenty-first centuries, and from two perspectives, expert and lay. It analyses four sources of language commentary to undertake two main comparisons. The first is a diachronic comparison of two language advice services: Le Courrier de Vaugelas (1868-1881) and the Courrier des internautes (2011-present, part of the Dire, Ne pas dire section of the Académie française’s website). Both sources publish readers’ questions about language and a response from an expert, allowing for the analysis of commentary from an expert and lay perspective. Expert language commentary has been well studied, in the form of usage guides, remarques, chroniques de langage and dictionary prefaces, for instance, but these sources are primarily monologic. Analysis of the two dialogic Q+A sources provides insight into both lay and expert commentary and the interaction between them.